2020
DOI: 10.1177/1744806920911543
|View full text |Cite
|
Sign up to set email alerts
|

GluA1 in central amygdala increases pain but inhibits opioid withdrawal-induced aversion

Abstract: The amygdala is important in regulation of emotion-associated behavioral responses both to positive reinforcing stimuli such as addicting opioids and to negative aversive stimuli such as fear and pain. Glutamatergic neurotransmission in amygdala plays a predominant role in amygdala neuronal circuits involved in these emotional responses. However, how specific glutamate receptors act to mediate these amygdala functions remains poorly understood. In this study, we investigated the role of GluA1 subunits of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Studies have found that GluA1-mediated synaptic plasticity plays an important role in the early development of Alzheimer’s disease [ 30 , 31 ]. In addition, drug addiction also increases GluA1 protein expression to promote the rewarding effects of drugs, such as opioid analgesics [ 32 ]. Nowadays, pain and its associated diseases remain a problem that plagues human society.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that GluA1-mediated synaptic plasticity plays an important role in the early development of Alzheimer’s disease [ 30 , 31 ]. In addition, drug addiction also increases GluA1 protein expression to promote the rewarding effects of drugs, such as opioid analgesics [ 32 ]. Nowadays, pain and its associated diseases remain a problem that plagues human society.…”
Section: Discussionmentioning
confidence: 99%
“…Rats receiving a control vector exhibited significant CPA behavior during naloxone-precipitated morphine withdrawal, while AAV-GluA1-infused rats showed reductions in aversive CPA behavior. These findings suggest that the neuroadaptive activation of GluA1 receptors in the CeA inhibits the aversive effects of opioid withdrawal (Cai et al, 2020).…”
Section: Role Of Neuroplasticity In the Central Nucleus Of The Amygda...mentioning
confidence: 75%
“…Changes in AMPA number, composition, phosphorylation state can modify synaptic strength and support cellular forms of learning (Chater and Goda, 2014). There are neuroadaptations of AMPA GluA1 receptor in the CeA and this change is associated with the conditioned aversive effects of opioid withdrawal (Cai et al, 2020). Additionally, glutamatergic plasticity in the CeA involves NMDA receptor mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is in line with our previous study showing an increased expression of GluA1 subunits of AMPARs in CeA neurons under CFA-induced persistent pain ( Hou et al, 2015 ). AMPARs are especially crucial for emotional events of learning and memory through activity-dependent synaptic strengthening via re-composition of GluA1 and GluA2 subunits ( Malinow and Malenka, 2002 ; Maren, 2005 ; Shepherd and Huganir, 2007 ; Bowers et al, 2010 ; Clem and Huganir, 2010 ; Krugers et al, 2010 ; McCool et al, 2010 ; Cole et al, 2012 ; Cai et al, 2013 , 2020 ). This AMPAR strengthening is achieved by switching from low conductance, GluA2-containing AMPARs to high conductance, homomeric GluA1 AMPARs ( Geiger et al, 1995 ; Isaac et al, 2007 ; Kauer and Malenka, 2007 ; Shepherd and Huganir, 2007 ; Polgar et al, 2008 ; Bowers et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%